Exciton absorption spectrum of thin films of (CsxK1-x)2CuCl3 solid solutions. - Kovalenko, E. N.; Yunakova, O. N.; Yunakov, N. N. (My University, 2024)
The absorption spectra of thin films of (CsxK1-x)2CuCl3 0≤х≤1 (T=90K) solid solutions in the spectral range 2–6 eV were studied. According to the analysis of the spectra, the formation of two types of compounds was observed and studied: 1) compounds at x=0 and in the range of 0.4≤х≤1 which are isostructural to Cs2CuCl3 and K2CuCl3; 2) compounds at x=0.2 which are isostructural to CsCu2Cl3. The excitonic spectra of (CsxK1-x)2CuCl3 0≤х≤1compounds are caused by transitions in the Cu+ ion. The linear concentration dependences of the spectral position of exciton bands in both types of compounds confirm the localization of excitons in sublattices containing Cu+ ions.
Keywords: thin films; absorption spectra; exciton